Supplementation of Moringa oleifera leaf powder orally improved productive performance by enhancing the intestinal health in rabbits under chronic heat stress. (October 2020) - Khalid, Abdur Rauf; Yasoob, Talat Bilal; Zhang, Zhen; Yu, Defu; Feng, Jiangyin; Zhu, Xiaofeng; Hang, Suqin
Abstract: Heat stress jeopardizes animal's growth and health mainly through induction of oxidative stress and inflammation. The current study investigated the effects of Moringa oleifera leaf powder (MOLP) supplementation on productive performance and intestinal health of rabbits under chronic heat stress (HS). Young New Zealand White rabbits (male) at the age of 32 weeks (n = 21, mean body weight of 3318 ± 171 g) for four weeks' period were reared on commercial pelleted diet and divided into three groups: control (CON, 25 °C), HS (35 ± 1 °C) and HS (35 ± 1 °C) with MOLP (HSM) supplemented orally (200 mg/kg body weight). The results demonstrated that rabbits in the HSM group had reduced rectal temperature, respiration rate and improved FCR due to improved daily gain and better crude fiber (NDF) digestibility ( P < 0.05) compared with HS group. MOLP improved intestinal integrity and function as indicated by lower serum diamine oxidase level and increased jejunal weight, length, villus height and ratio of villus height to crypt depth than heat-stressed rabbits. MOLP reversed the increased levels of serum cortisol, metabolic indicators i.e. glucose, insulin, and reduced concentrations of serum triiodothyronine. MOLP supplementation also significantly down-regulated the mRNA expression of tumor necrosis factor alpha (α), heat shock protein A2, glutathione peroxidase-1, interleukin (IL)-1α and increased the expression of IL-6. In conclusion, MOLP supplementation could enhance intestinal health along with production and metabolic indicators by alleviating the oxidative stress and inflammatory response in small intestine of hyper-thermic rabbits. Highlights: Supplementation of Moringa oleifera leaf powder (MOLP) orally reduced RT, RR and improved the productive performance under HS. MOLP supplementation enhanced intestinal integrity as depicted by improved villus height and reduced serum DAO level under HS. MOLP supplementation decreased the levels of serum cortisol, glucose, insulin and increased triiodothyronine level under HS. MOLP supplementation decreased mRNA expression of TNF-α, HSPA2, GPx-1, IL-1α and increased IL-6 in heat stressed NZW rabbits.